Additions of ammonium sulfate and urease inhibitor with urea to improve spring wheat and sugar beet yield. Issue 10 (24th August 2018) - Chatterjee, Amitava
ABSTRACT: Additions of ammonium sulfate and urease inhibitor with urea might have potential to increase yield and quality due to increased supply of sulfur (S) and reduction in volatilization loss of nitrogen (N), respectively. Treatments consisting, (i) urea alone, (ii) urea with ammonium sulfate (UAS) and (iii) homogeneous granular fertilizer containing urea and ammonium sulfate (HBU), and (iv) urease inhibitor treated urea (UI), at two application rates, 134 and 168 kg N ha −1, were compared for spring wheat ( Triticum aestivum L.) and sugar beet ( Beta vulgaris L.) production at Glyndon and Ada of Minnesota, USA, during 2014–2015. For both crops, additions of UI had increased yield due to higher soil N availability over urea only in 2015. In 2014, UI also increased the grain protein content over urea and UAS increased sugar content only over HBU in 2015. Spring wheat and sugarbeet yield and quality response to urease inhibitor or supply of S in the form of UAS depends on soil and climatic factors.